MOTIVASI DAN KEBIASAAN SISWA SELAMA PEMBELAJARAN DARING HUBUNGANNYA DENGAN HASIL BELAJAR SISWA KELAS IV - Victorria Yunus; Budiman Tampubolon; Tahmid Sabri (Universitas Tanjungpura, 2020)
Abstract This research aims to find out the relationship between learning motivation and learning habits together to the learning outcomes of grade IV students of 17 Pontianak City Elementary School. The research method used is quantitative descriptive with a form of correlation study research. The population in this study was grade IV students of SDN 17 Pontianak. The samples in this study were determined using probabilty sampling techniques with random sampling type and selected grade IVC SDN 17 Pontianak Kota. The source of this research data is grade IVC students of SDN 17 Pontianak Kota and the average rapot document. The data is a poll score of learning motivation and learning habits and average rapot scores. The results showed 79.16% of students' learning motivation was in the good category, students' learning habits were 79.87% in the good category, and 83.96% of study results fell into the excellent category. The correlation between learning motivation and learning outcomes was 0.550 in the moderate category. The correlation between learning habits and learning outcomes of 0.521 fell into the moderate category. The correlation of learning motivation and learning habits was 0.458. The correlation between learning motivation and habits together with learning outcomes of 0.627 fell into the strong category. Keywords : Learning Motivation, Learning Habits, and Learning Outcomes.